Engineering of glucose-stimulated insulin secretion and biosynthesis in non-islet cells. - Hughes, S D (1992)
The high-capacity glucose transporter known as GLUT-2 and the glucose phosphorylating enzyme glucokinase are thought to be key components of the "glucose-sensing apparatus" that regulates insulin release from the beta cells of the islets of Langerhans in response to changes in external glucose concentration. AtT-20ins cells are derived from anterior pituitary cells and are like beta cells in that they express glucokinase and have been engineered to secrete correctly processed insulin in response to analogs of cAMP, but, unlike beta cells, they fail to respond to glucose and lack GLUT-2 expression. Herein we demonstrate that stable transfection of AtT-20ins cells with the GLUT-2 cDNA confers glucose-stimulated insulin secretion and glucose regulation of insulin biosynthesis and also results in glucose potentiation of the secretory response to non-glucose secretagogues. This work represents a first step toward creation of a genetically engineered "artificial beta cell."